Prediction of the wine polyphenol metabolic space: An application of the Phenol‐Explorer database. Issue 3 (9th October 2013) - Boto‐Ordóñez, María; Rothwell, Joseph A.; Andres‐Lacueva, Cristina; Manach, Claudine; Scalbert, Augustin; Urpi‐Sarda, Mireia
<x xml:space="preserve">Abstract</x> Scope Knowledge of in vivo polyphenol metabolites derived from the consumption of red wine could be key to understanding its health benefits. This work aimed to predict the wine polyphenol metabolic space in biofluids by using all available data compiled in the Phenol‐Explorer database. Methods and results A search strategy was developed for Phenol‐Explorer to obtain the widest range of metabolites related to wine consumption. A total of 97 metabolites have been described in intervention studies with wine and related products (n = 37), and after consumption of pure compounds known to be wine constituents (n = 90). These 97 metabolites, derived from host and microbial metabolism of several classes of polyphenols, were found in plasma and urine samples and some of them have demonstrated higher or lower biological activities than the parent compound in in vitro studies. The metabolites have been linked to generate, for the first time, a global pathway map of wine in vivo polyphenol metabolism. Conclusion The retrieval of the widest range of metabolites so far described and their assembly as a metabolic pathway map could aid the identification of possible biomarkers of wine consumption and improve current understanding of the health effects of wine consumption.